2020
DOI: 10.51791/njap.v45i4.543
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Farm management risk factors of contracting haemoparasitic infections in Pastoralist and Sedentary cattle in Soba Local Government Area, Kaduna State, Nigeria

Abstract: The major cattle management system observed in Soba Local Government Area was pastoral husbandry system. Under this system, cattle were extensively grazed on established forages of Kaduna State forests and were exposed to various arthropod vectors of haemoparasites. These haemoparasites are a serious threat to food security in Soba LGA due to their influence on cattle productivity. Questionnaires were used in assessing some farm management risk factors of contracting haemoparasitic infections in both pastorali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Livestock husbandry and management systems with regard to Coxiella infection in Nigeria Tukur et al (2014), in a study to determine the seroprevalence of C. burnetii in cattle in Kaduna metropolis, reported that cattle with no ectoparasites control programme had higher seroprevalence against C. burnetii and that exotic breeds of cattle were negative for Q fever antibodies as they were suspected of having strict external parasites control. Furthermore, Danbirni et al (2018) reported that the major cattle management system they observed in Soba Local Government Area of Kaduna State was the pastoral husbandry system in which cattle were extensively grazed on wild forages and this exposed the cattle and even the small ruminants under their control to various arthropod vectors of haemoparasites, bacterial and viral disease among others. Similarly, Kaltungo (2013;2018a2018b) reported pastoralists and small ruminant holders keeping their livestock under traditional methods with herds and flocks from neighbours mixing freely.…”
Section: Risk Factors To Coxiella Infection In Humansmentioning
confidence: 99%
“…Livestock husbandry and management systems with regard to Coxiella infection in Nigeria Tukur et al (2014), in a study to determine the seroprevalence of C. burnetii in cattle in Kaduna metropolis, reported that cattle with no ectoparasites control programme had higher seroprevalence against C. burnetii and that exotic breeds of cattle were negative for Q fever antibodies as they were suspected of having strict external parasites control. Furthermore, Danbirni et al (2018) reported that the major cattle management system they observed in Soba Local Government Area of Kaduna State was the pastoral husbandry system in which cattle were extensively grazed on wild forages and this exposed the cattle and even the small ruminants under their control to various arthropod vectors of haemoparasites, bacterial and viral disease among others. Similarly, Kaltungo (2013;2018a2018b) reported pastoralists and small ruminant holders keeping their livestock under traditional methods with herds and flocks from neighbours mixing freely.…”
Section: Risk Factors To Coxiella Infection In Humansmentioning
confidence: 99%
“…In order to understand the epidemiology of tuberculosis in animals, a good comprehension of the husbandry and management systems of the animals is important. Livestock production in Nigeria especially that as practiced by the pastoralists, is characterized by extensive management system while the animals under the elite herds are being managed partially under semiintensive system (Saidu, et al, 1991;Danbirni, 2018). This involves the cattle and to a certain extent sheep being moved from one place to another.…”
Section: Characteristics Of Livestock Production In Nigeriamentioning
confidence: 99%